PSMC2 Regulates Cell Cycle Progression Through the p21/Cyclin D1 Pathway and Predicts a Poor Prognosis in Human Hepatocellular Carcinoma - Liu, Yiwei; Chen, Hairong; Li, Xiangcheng; Zhang, Feng; Kong, Lianbao; Wang, Xuehao; Bai, Jin; Wu, Xiaofeng (Frontiers in Oncology, 2021)
Proteasome 26S subunit ATPase 2 (PSMC2) plays a pathogenic role in various cancers. However, its function and molecular mechanism in hepatocellular carcinoma (HCC) remain unknown. In this study, tissue microarray (TMA) analysis showed that PSMC2 is highly expressed in HCC tumors and correlates with poor overall and disease-free survival in HCC patients. Multivariate Cox regression analysis revealed that PSMC2 is an independent prognostic factor for HCC patients. Furthermore, our results showed that PSMC2 knockdown inhibited cell proliferation and suppressed tumorigenesis in vivo. Knockdown of PSMC2 increased the expression of p21 and therefore decreased the expression of cyclin D1. Dual-luciferase reporter assays indicated that depletion of PSMC2 significantly enhanced the promoter activity of p21. Importantly, PSMC2 knockdown-induced phenotypes were also rescued by downregulation of P21. Taken together, our data suggest that PSMC2 promotes HCC cell proliferation and cell cycle progression through the p21/cyclin D1 signaling pathway and could be a promising diagnostic and therapeutic target for HCC patients.